China should not massively reclaim new farmland. (March 2018) - Xin, Liangjie; Li, Xiubin
Abstract: To protect farmland and ensure national food security and social stability, China implemented the Dynamic Balance of Total Farmland Area (DBTFA) policy in 1998. From 2000–2013, the amount of newly reclaimed land reached 2.47 million hectares. This massive reclaiming of farmland appeared to effectively halt the rapid loss of farmland in China. However, four aspects suggest that the DBTFA policy has become outdated and economically ineffective. First, bumper grain harvests and imports have provided China with an ample domestic food supply, which means it is no longer threatened by grain shortages; second, China does not have much land left suitable for farmland reclamation; third, the cost of land reclamation is very high; fourth, land abandonment is common in China. The massive amounts of newly reclaimed farmland have not been utilized effectively. Therefore, the key goal of the current farmland protection policy should be to protect high-quality farmland instead of reclaiming new farmland.